Examining the Spatiotemporal Disruption to Gaze When Using a Myoelectric Prosthetic Hand. Issue 4 (4th July 2018) - Parr, J. V. V.; Vine, S. J.; Harrison, N. R.; Wood, G.
ABSTRACT: The aim of this study was to provide a detailed account of the spatial and temporal disruptions to eye-hand coordination when using a prosthetic hand during a sequential fine motor skill. Twenty-one able-bodied participants performed 15 trials of the picking up coins task derived from the Southampton Hand Assessment Procedure with their anatomic hand and with a prosthesis simulator while wearing eye-tracking equipment. Gaze behavior results revealed that when using the prosthesis, performance detriments were accompanied by significantly greater hand-focused gaze and a significantly longer time to disengage gaze from manipulations to plan upcoming movements. The study findings highlight key metrics that distinguish disruptions to eye-hand coordination that may have implications for the training of prosthesis use.